The hiding hyena \ Antonia Ringbom - Ringbom, Antonia (Estados Unidos de América: Somondoco Press)
I´m the killer, oh look at those loverly girls!, ugh! moreo and more coffins are needed, whats es this deadly disease?, oh! old uncles have NO rigth to touch young firls!
Includes question guide
Col. Educ
Keywords: 1. CUENTOS 2. THE HIDING HYENA 3. LITERATURE 4. EDUCATION